Challenges in adapting a stroke unit in a middle-income country: warning about costs and underfunding to achieve the Brazilian Ministry of Health’s benchmark - Ferreira, Natalia Cristina; Luvizutto, Gustavo José; Bazan, Silméia Garcia Zanati; Bonome, Luana Aparecida Miranda; Winckler, Fernanda Cristina; dos Santos, Daniel Fabiano Barbosa; Chiloff, Cristiane Lara Mendes; Modolo, Gabriel Pinheiro; de Freitas, Carlos Clayton Macedo; Barretti, Pasqual; Lange, Marcos Christiano; Minicucci, Marcos Ferreira; et al. (Frontiers in Public Health, 2024)
Background: Since the implementation of the stroke care line in Brazil, the relationship (adequacy) of costs spent during hospitalization with the Brazilian Ministry of Health indicators for a stroke unit have not yet been analyzed. Aims: This study aimed to assess the adequacy of a comprehensive stroke center for key performance indicators and analyze the costs involved in hospitalization. We verified the association between stroke severity at admission and care costs during hospitalization. Methods: A retrospective medical chart review of 451 patients was performed using semiautomatic electronic data from a single comprehensive stroke center in Brazil between July 2018 and January 2020. Clinical and resource utilization data were collected, and the mean acute treatment cost per person was calculated. The Kruskal–Wallis test with Dunn’s post-test was used to compare the total costs between stroke types and reperfusion therapies. A robust linear regression test was used to verify the association between stroke severity at hospital admission and the total hospitalization costs. Good adequacy rates were observed for several indicators. Results: Data from 451 patients were analyzed. The stroke unit had good adaptation to key performance indicators, but some critical points needed revision and improvement to adapt to the requirements of the Ministry of Health. The average total cost of the patient's stay was the USD 2,637.3, with the daily hospitalization, procedure, operating room, and materials/medication costs equating to USD 2,011.1, USD 220.7, USD 234.1, and USD 98.8, respectively. There was a positive association between the total cost and length of hospital stay (P<0.001). Conclusions: The stroke unit complied with most of the main performance indicators proposed by the Brazilian Ministry of Health. Underfunding of the costs involved in the hospitalization of patients was verified, and high costs were associated with the length of stay, stroke severity, and mechanical thrombectomy.